Listeria monocytogenes Attachment to and Detachment from Stainless Steel Surfaces in a Simulated Dairy Processing Environment - Poimenidou, Sofia (American Society for Microbiology (ASM), 2009)

(untitled)
The presence of pathogens in dairy products is often associated with contamination via bacteria attached to food-processing equipment, especially from areas where cleaning/sanitation is difficult. In this study, the attachment of Listeria monocytogenes on stainless steel (SS), followed by detachment and growth in foods, was evaluated under conditions simulating a dairy processing environment. Initially, SS coupons were immersed in milk, vanilla custard, and yogurt inoculated with the pathogen (10(7) CFU/ml or CFU/g) and incubated at two temperatures (5 and 20°C) for 7 days. By the end of incubation, cells were mechanically detached from coupons and used to inoculate freshly pasteurized milk which was subsequently stored at 5°C for 20 days. The suspended cells in all three products in which SS coupons were immersed were also used to inoculate freshly pasteurized milk (5°C for 20 days). When SS coupons were immersed in milk, shorter lag phases were obtained for detached than for planktonically grown cells, regardless of the preincubation temperature (5 or 20°C). The opposite was observed when custard incubated at 20°C was used to prepare the two types of inocula. However, in this case, a significant increase in growth rate was also evident when the inoculum was derived from detached cells. In another parallel study, while L. monocytogenes was not detectable on SS coupons after 7 days of incubation (at 5°C) in inoculated yogurt, marked detachment and growth were observed when these coupons were subsequently transferred and incubated at 5°C in fresh milk or/and custard. Overall, the results obtained extend our knowledge on the risk related to contamination of dairy products with detached L. monocytogenes cells.